Effects Of Process Parameters On Geobacter Sulfurreducens And Bacillus Subtilis From Dewatered Sludge For Electricity Generation In Membrane – Less Microbial Fuel Cell - Sabri, Muhammad Najib Ikmal Mohd (2022)
The membrane-less microbial fuel cell (ML-MFC) is a cutting-edge renewable energy technology that might help to solve the world's energy dilemma. Electrogenic bacteria (EB) which are Geobacter sulfurreducens (GS) and Bacillus subtilis (BS) served as a biocatalyst in the ML-MFC, allowing it to create power electrochemically. The ML-MFC employed dewatered sludge from two separate wastewater treatment plants (A – IWK Juru and B – IWK Butterworth). From the analysis of elements, sludge A showed a large amount of magnesium and calcium elements than sludge B which facilitate electron transfer in ML - MFC. The performance of the ML-MFC utilising sludge A and B as substrate were then assessed using the one-factor-at-a-time (OFAT) approach, followed by response surface methodology (RSM) using a quadratic model through Central Composite Design. The best pH 9, electrode distance (ED) 4 cm, the moisture content (MC) 40 % (v/w) and the temperature 40 ℃ obtained the optimum responses; biomass (1.88 mg/L), COD removal 46.52 % (202 mg/L) and power density ( 7.406 mW/m2) in the preliminary OFAT research. The voltage was effectively enhanced by utilising the optimal conditions recommended by the RSM. As stated by the kinetics growth of EB shows that in RSM parameter conveys a significant specific growth rate (μ) (21.005 mg(Lh−1))and doubling time (Td) (0.033mgh-1).